TRest as a New Diagnostic Variable for Chronic Exertional Compartment Syndrome of the Forearm: A Prospective Cohort Analysis of 124 Athletes. Issue 6 (November 2018) - Barrera-Ochoa, Sergi; Correa-Vazquez, Eva; Gallardo-Calero, Irene; Haddad, Sleiman; Sallent, Andrea; Soldado, Francisco; Campillo-Recio, David; Mir-Bullo, Xavier
Abstract : Objectives: To measure the accuracy of currently used intracompartmental pressure (ICP) diagnostic variables for forearm chronic exertional compartment syndrome (CECS) and a new ICP diagnostic variable, TRest, the recovery time between the maximum ICP and return to resting pressure. Design: Retrospective cohort. Level evidence IV. Setting: University-affiliated tertiary hospital. Participants: Patients with suspected forearm CECS, 1990 to 2014. Interventions: All patients underwent physical examination and exertional stress test, preceded and followed by measuring ICP in all suspicious CECS. Surgery was proposed when indicated. Minimum follow-up was 18 months. Final diagnosis was established at the final follow-up. Main Outcome Measures: Intracompartmental pressure measurements: PRest (baseline/pre-exercise pressure), P1 min (pressure 1 minute after exercise), P5 min (pressure 5 minutes after exercise), and TRest . Patients rated their pain and completed Quick-DASH in all follow-ups. Patients ultimately were classified into 4 groups (true positives, true negatives, false positives, and false negatives) for each ICP measurement relative to the final diagnosis. Sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated. Results: A total of 124 male athletes were diagnosed with CECS, 27 bilateral. Accuracy with standard ICP diagnostic variables was lower (sensitivity 73.5%, specificity 84.2%, positive predictive value 97%, and negative predictive value 31.4%) than with TRest (SN 100%, SP 94.7%, PPV 99.3%, and NPV 100%); 23% of patients would have been missed following the standard ICP diagnostic criteria. Conclusions: Diagnostic thresholds for current standard ICP measurements should be lowered. TRest, a new measure, might be more accurate.